Green Innovation and Firm Performance: The Ecological Modernization Perspective - Mohd Zahari, Fadhilah; Ramayah, T (UUM Press, 2017)
Green innovation is becoming an essential business strategy in the 21st century as it brings sustainable environment and economic prosperity hand in hand. Consequently, the impact of green innovation on firm performance has drawn enormous attention among the scholars for the past few decades, aiming at empirically justify the positive implications of being green in business. However, the analysis from the ecological modernization perspective remains limited, although the focus on preventive approach to achieve environmental and economic improvement is the central argument of this theoretical lens. This study tackles the above issue by examining the performance outcomes of green innovation adoption in view of ecological modernization perspective. A quantitative, survey-based study collected data from 130 Malaysian manufacturing firms, which was subsequently analyzed using SmartPLS 2.0. The findings generally corroborate the positive implications of green innovation on firm performance in the aspects of environment, economic and competitive advantage. Likewise, EM perspective fits in offering plausible insights of the findings, hence entails the alternative ground to be employed in other studies of the like.